Proteomic Signatures of Human Visceral and Subcutaneous Adipocytes - Hruska, Pavel; Kucera, Jan; Pekar, Matej; Holéczy, Pavol; Mazur, Miloslav; Buzga, Marek; Kuruczova, Daniela; Lenart, Peter; Fialova Kucerova, Jana; Potesil, David; Zdrahal, Zbynek; Bienertova-Vasku, Julie (The Journal of clinical endocrinology and metabolism, 2022)
CONTEXT: Adipose tissue distribution is a key factor influencing metabolic health and risk in obesity-associated comorbidities. OBJECTIVE: Here we aim to compare the proteomic profiles of mature adipocytes from different depots. METHODS: Abdominal subcutaneous (SA) and omental visceral adipocytes (VA) were isolated from paired adipose tissue biopsies obtained during bariatric surgery on 19 severely obese women (body mass index > 30 kg/m2) and analyzed using state-of-the-art mass spectrometry. Differential expression analysis and weighted gene co-expression network analysis (WGCNA) were performed to investigate proteome signature properties and to examine a possible association of the protein expression with the clinical data. RESULTS: We identified 3686 protein groups and found 1140 differentially expressed proteins (adj. P value < 0.05), of which 576 proteins were upregulated in SA and 564 in VA samples. We provide a global protein profile of abdominal SA and omental VA, present the most differentially expressed pathways and processes distinguishing SA from VA, and correlate them with clinical and body composition data. We show that SA are significantly more active in processes linked to vesicular transport and secretion, and to increased lipid metabolism activity. Conversely, the expression of proteins involved in the mitochondrial energy metabolism and translational or biosynthetic activity is higher in VA. CONCLUSION: Our analysis represents a valuable resource of protein expression profiles in abdominal SA and omental VA, highlighting key differences in their role in obesity.
Keywords: Adipocytes; tukové buňky; adipose tissue; proteomika; nitrobřišní tuk; Omentum; Subcutaneous Fat, Abdominal; Middle Aged; obesity; Adult; genové regulační sítě; Gene Regulatory Networks; bariatrická chirurgie; Proteomics; ženské pohlaví; Humans; Intra-Abdominal Fat; adipocytes; omentum; podkožní břišní tuk; visceral adipose tissue; subcutaneous adipose tissue; lidé středního věku; metabolism; Bariatric Surgery; dospělí; Female; Obesity, Morbid; lidé; morbidní obezita